AL-UKHUWAH AL-IJTIMA’IYAH WA AL-INSANIYAH - Hamidah Hamidah (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2012)
The paradigm of freedom and religious tolerance in Islam contains teachings about human equality. Above equation can be formed brotherhood and friendship among religious social life based on humanity in order to create social order together. Thus from the side of humanity, Islam does not recognize exclusiveness, and from the side of faith, Islam does not recognize intolerance. In social interaction, Islam outlines the people not to argue with the followers of other religions but in a polite way, and ethical, and they should do well, and be fair to other religious communities. Expansion of the actual and empirical interpretation of religious teachings and by adjusting the reality aspects of socioeconomic, political and cultural socialization and assimilation is an effort and cultural assimilation of religious values in the society and the nation in particular in the development, so that religion can be played in development. And the vastness of religious insight of the religion will grow an attitude and an open and inclusive approach to social problems of mankind and humanity.Paradigma kebebasan dan toleransi beragama dalam lslam mengandung ajaran tentang persamaan manusia. Di atas persamaan ini dapat dibentuk persaudaraan dan persahabatan antar pemeluk agama dalam kehidupan sosial berdasarkan kemanusiaan demi terwujudnya ketertiban sosial bersama. Dengan demikian dari sisi kemanusiaan, lslam tidak mengenal eksklusivisme, dan dari sisi akidah, Islam juga tidak mengenal intoleransi. Dalam pergaulan sosial lslam menggariskan kepada umatnya yaitu tidak boleh berbantahan dengan penganut agama lain melainkan dengan cara yang sopan dan etis, dan mereka boleh berbuat baik dan berlaku adil terhadap komunitas agama lain. Perluasan penafsiran ajaran agama secara aktual dan empiris dengan merelevansikannya dengan aspek-aspek realitas sosial ekonomi, politik dan budaya merupakan upaya sosialisasi dan inkulturasi nilai-nilai agama dalam kehidupan bermasyarakat dan berbangsa khususnya dalam pembangunan, sehingga agama dapat diperankan dalam pembangunan. Dan keluasan wawasan penganut agama akan ajaran agamanya akan menumbuhkan sikap dan pandangan yang terbuka dan inklusif terhadap masalah-masalah sosial dan kemanusiaan umat manusia.